KANDUNGAN KIMIA DARI LIMBAH LUMPUR INSTALASI PENGOLAHAN AIR MINUM UNTUK BETON GEOPOLIMER DENGAN XRF - Nuryanti Nuryanti; Ridha Arizal; Dian Arrisujaya (JURNAL SAINS NATURAL, 2017)
Chemical Containt of Waste Water Installation of Drinking Water Treatment for Geopolymer Concrete by XRF Preparation of geopolymer concrete from waste water installation of drinking water treatment (WIDWT) was manufactured in accordance with SNI. Specimen of size 5 x 5 x 5 cm cubes was used for the concretes. The mortar material consisted of binders, activator, aggregate (fine sand) and water (60% of aggregate and 40% of activators and binders). The composition of the activator and binder mixture were 1: 2; 1: 1,5; 1: 1; 1.5: 1; and 2: 1. The results of the comparison of binders A and B were 4.2: 1 and 6.5: 1. The binders were divided into 2 types: A binder (sludge of WIDWT was dried with oven at 105oC for 24 hours) and B Binder (sludge of WIDWT was dried by kiln at 650oC for 6 hours). The highest compressive strength test was 10.00 MPa on binder A with the ratio of activator and binder 1: 1 and Si: Al ratio (4.2: 1). Binder B with a compressive strength of 9.87 MPa with the ratio of activator and binder 1.5: 1 and Si: Al ratio (6.5: 1). Samples of IPAM sludge waste were tested by X-Ray Fluorescence (XRF), compressive strength testing of mortar geopolymer with Toni-Technik compressive strength test. The highest value of compressive strength appropriated to SNI 03-0691-1996 in class D which can be applied for City Park.Keywords: geopolymer, WIDWT, XRF, activator, binder ABSTRAK Pembuatan beton geopolimer dari limbah instalasi pengolahan air minum (IPAM) telah dilakukan. Beton geopolimer dibuat sesuai dengan SNI pembuatan mortar geopolimer dengan ukuran 5 x 5 x 5 cm. Bahan mortar terdiri dari binder, larutan aktivator dan agregat (pasir halus) serta air dengan perbandingan 60% (agregat) dan 40%(aktivator dan binder). Parameter variasi campuran aktivator dan binder yaitu 1:2; 1:1,5; 1:1; 1,5:1; dan 2:1. Binder dibagi menjadi 2 jenis yaitu Binder A (lumpur IPAM yang dikeringkan dengan oven pada suhu 105oC selama 24 jam) dan Binder B (lumpur IPAM yang dikeringkan dengan tanur pada suhu 650oC selama 6 jam). Hasil perbandingan binder A dan B adalah 4,2:1 dan 6,5:1. Hasil uji kuat tekan tertinggi sebesar 10,00 Mpa pada binder A dengan perbandingan aktivator dan binder 1:1 dengan perbandingan Si:Al (4,2:1). Binder B dengan kuat tekan 9,87 Mpa dengan perbandingan aktivator dan binder 1,5:1 dengan perbandingan Si:Al (6,5:1). Sampel limbah lumpur IPAM diuji dengan X-Ray Flourescene (XRF), pengujian kuat tekan mortar geopolimer dengan alat uji kuat tekan merk Toni-Technik. Nilai kuat tekan tertinggi memasuki persyaratan mutu SNI 03-0691-1996 pada kelas D yang bisa diaplikasikan untuk taman kota.Kata Kunci: geopolimer, IPAM, XRF, aktivator, binder